Two-component coating and method of use thereof and flexible ablative thermal protection coating
By forming a borosilicate glass phase carbon layer through cross-linking and curing of a two-component coating, the problem of insufficient flexibility and ablation product strength of existing coatings at room temperature is solved, achieving a robust thermal protection effect at high temperatures, which is suitable for equipment and cables near the flames of missile and rocket engines.
Patent Information
- Application Number
- CN202610858406.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-15
- Publication Date
- 2026-08-25
AI Technical Summary
Existing thermal protective coatings lack sufficient flexibility at room temperature and the mechanical strength of ablation products is inadequate, resulting in poor thermal protection for equipment and cables near missile engine flames and increasing ineffective loads.
A two-component coating is used. Component A contains organosilicon-modified diol oligomer, polyester diol, catalyst, boron-containing flame retardant filler and ceramic filler, while component B contains diisocyanate and polyisocyanate. Through cross-linking and curing, a coating ablation product with borosilicate glass phase is formed, which enhances mechanical strength and flexibility.
It rapidly forms a robust borosilicate glass phase carbon layer under high-temperature ablation, providing excellent mechanical strength and thermal protection performance, resisting engine vibration and aerodynamic stripping, and is suitable for thermal protection of equipment and cables near rocket and missile ignition sources.
Smart Images

Figure CN122628655A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of coatings and coatings, and relates to a thermal protective coating and coating, specifically to a two-component coating and its application method, as well as a flexible ablation-type thermal protective coating. Background Technology
[0002] Equipment and cables near the engine flames of rockets and missiles are exposed to extremely strong heat flux radiation, with peak heat flux density on the equipment surface exceeding 500 kW / m², and surface temperatures exceeding 1000°C after short-term heating. Such high temperatures can damage components and instruments within the control system, ultimately leading to system malfunctions and control failures.
[0003] Because there are numerous instruments and cables near the missile engine, with diverse and complex shapes and sizes, and the equipment is compactly distributed within the missile body in a confined space; furthermore, these internal instruments and equipment require frequent inspection and maintenance during the storage period, necessitating frequent disassembly and reassembly of their external heat-resistant structures. Therefore, the simplest and most efficient method is to cover the equipment and cables with a flexible heat-resistant coating that closely conforms to their shape, much like "clothing."
[0004] In existing technologies, polymer-based heat-resistant materials are a widely used type of heat protection coating in aerospace due to their low density, ease of construction, and good resistance to instantaneous high temperatures.
[0005] For example, phenolic resin-based coatings, thanks to their high aryl content, can achieve a highly graphitized carbon layer structure after ablation, resulting in high char residue and good mechanical strength of the ablated material. Similarly, other polymers with high aryl content, such as polyarylethers and benzoxazines, also have similar advantages. However, these high-aryl-content polymers are generally rigid at room temperature, lacking elasticity and toughness, and therefore are not suitable as thermal protective coatings for projectiles and rockets. Equipment near projectile and rocket ignition sources, especially cables, requires thermal protective coatings that are flexible at room temperature.
[0006] Compared to the aforementioned crosslinked aromatic polymers, existing thermal protective coatings using room-temperature flexible polymers as the matrix exhibit significant drawbacks during the ablation process. Specifically, the mechanical strength of the ablation products is insufficient, making them highly susceptible to damage under engine vibration and aerodynamic stripping, thus severely weakening their thermal protective performance. Therefore, to ensure effective thermal protection in practical applications, these coatings require a large thickness margin, significantly increasing the overall weight of the thermal protective coating and consequently increasing the ineffective load on projectiles.
[0007] In summary, the flexibility of a coating at room temperature and the high mechanical strength of its ablation products are two important technical indicators for thermal protective coatings used in equipment and cables near missile engine flames. However, current thermal protective coatings present a contradiction between room temperature flexibility and the mechanical strength of ablation products; that is, there are few reports on ablation-type thermal protective coatings that possess both room temperature flexibility and ensure high mechanical strength of ablation products. Summary of the Invention
[0008] To fill the above gaps, the present invention provides a two-component coating, which produces an ablation-type thermal protective coating that is flexible at room temperature and exhibits excellent mechanical properties after ablation.
[0009] A two-component coating is disclosed, which consists of component A and component B;
[0010] Component A comprises, by weight, the following:
[0011] 5-20 parts of organosilicon-modified diol oligomers;
[0012] 10-30 parts of polyester glycol;
[0013] 0.1-1 part of catalyst;
[0014] 5-15 parts of boron-containing flame-retardant filler;
[0015] 5-10 parts of ceramic filler;
[0016] 20-60 parts solvent;
[0017] The boron flame retardant in the boron-containing flame retardant filler is zinc borate, borax, sodium borate, calcium borate, etc. Triphenyl borate , boron Tributyl acetate One or more of the following; the ceramic filler is aluminum dihydrogen phosphate and silica powder;
[0018] Component B comprises, by weight, the following:
[0019] 50-90 parts of diisocyanate;
[0020] 10-40 parts of polyisocyanate.
[0021] Preferably, component A comprises, by weight, the following:
[0022] 5-15 parts of organosilicon-modified diol oligomer;
[0023] 15-25 parts of polyester glycol;
[0024] 0.1-0.5 parts of catalyst;
[0025] 5-10 parts of boron-containing flame-retardant filler;
[0026] 6-8 parts of ceramic filler;
[0027] 30-40 parts solvent;
[0028] Preferably, component B comprises, by weight:
[0029] 60-75 parts of diisocyanate;
[0030] 15-30 parts of polyisocyanate.
[0031] Furthermore, the organosilicon-modified diol oligomer is prepared by a two-step method: the first step involves reacting a cyclic siloxane with bis(3-aminopropyl)tetramethyldisiloxane at a molar ratio of 1:1.5-2, using a quaternary ammonium salt as a catalyst, at 60-120°C for 8-15 hours to prepare an amino-terminated siloxane oligomer; the second step involves reacting the reaction product from the first step with a cyclic carbonate at a molar ratio of 1:1-1.5, at 70-100°C for 5-10 hours to obtain the organosilicon-modified diol oligomer.
[0032] Preferably, the cyclic siloxane is one of hexamethylcyclotrisiloxane D3, octamethylcyclotetrasiloxane D4, and decamethylcyclopentasiloxane D5;
[0033] The quaternary ammonium salt is one of tetrabutylammonium chloride, tetrabutylammonium fluoride, and hexadecyltrimethylammonium chloride;
[0034] The cyclic carbonate is one of methyl vinylene carbonate, ethylene carbonate, and propylene carbonate.
[0035] Preferably, the polyester diol is one of polyethylene adipate diol, 1,4-butanediol adipate diol, polycarbonate diol, and polybutylene sebacate diol, with a molecular weight Mw of 1000-3000.
[0036] Furthermore, the boron-containing flame-retardant filler also contains an organophosphorus flame retardant, which is one or more of ammonium polyphosphate, pentaerythritol phosphate, triphenylphosphonate, and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO).
[0037] Preferably, the silica powder is one or more of low-melting-point glass powder (melting point 400-600℃), mica powder, and silica micro powder.
[0038] The catalyst in component A is one of organotin catalyst, tertiary amine catalyst, or bismuth catalyst (bismuth neodecanoate); the solvent in component A is one of ethyl acetate, butyl acetate, dimethyl carbonate, or diethyl carbonate.
[0039] Of course, some conventional additives can also be added to component A above, such as defoamers, drying agents, anti-hydrolysis agents, leveling agents, inorganic pigments, etc. For example, melamine and its salts or dicyandiamide additives can be added to the boron-containing flame-retardant filler, and talc additives can be added to the ceramic filler. Technicians can select according to the actual situation, and the dosage is also the conventional dosage, which can be determined by technicians according to the actual situation.
[0040] Preferably, the diisocyanate is one or more of toluene diisocyanate, diphenylmethane diisocyanate (MDI), liquefied MDI (such as Wanhua CDMDI-100L, MDI-100LL), hexamethylene diisocyanate, and isophorone diisocyanate.
[0041] The polyisocyanate is one or more of the following: TDI trimer (such as TT-150B, TT-350B), HDI trimer (Wanhua HDT-90, HDT-LV, etc.), and polymeric MDI (Wanhua's PM-200, PM-400).
[0042] Of course, a reactive dehydrating agent can also be added to component B of the present invention. Technicians can select the appropriate agent based on the actual situation, and the dosage is also the conventional dosage, which can be determined by technicians based on the actual situation.
[0043] The publicly disclosed method for using two-component coatings is to mix component A and component B at a weight ratio of 100:5-15, and then spray the mixture onto the substrate surface multiple times according to a spray-dry process. Each spray is dried at a temperature of 60-100℃ for more than 10 minutes. After multiple sprays and dryings, a flexible ablation-type thermal protective coating of a specified thickness is finally obtained.
[0044] The substrate is one of aramid fabric, basalt fiber fabric, glass fiber fabric, or polyimide fiber fabric.
[0045] The disclosed flexible ablation-type thermal protective coating prepared by the above-mentioned method has the following characteristics: Shore A hardness is less than 50, elongation at break is greater than 100%, tensile strength is greater than 4 MPa, and UL-94 flame retardancy rating is V-0.
[0046] The thermal protective coating can form a coating ablation product containing a borosilicate glass phase within 2 minutes under high temperature ablation above 1000℃. The thermal conductivity of the coating ablation product is 0.5-1.2 W / m·K, and the compressive strength of the coating ablation product is above 1.1 MPa.
[0047] The principle of this application is as follows:
[0048] The organosilicon-modified diol oligomer in component A is an oligomer with Si-O-Si segments in its molecular chain and C-OH-terminated ends. It has good compatibility with polyester diol and can be uniformly dispersed in the coating as a film-forming substance, and can uniformly coat each solid filler component.
[0049] In the heat-protective coating prepared by cross-linking and curing components A and B, the organosilicon-modified diol oligomer uniformly coated with solid filler has siloxane segments that can increase the flexibility of the coating matrix, making the heat-protective coating flexible, foldable and bendable under normal conditions.
[0050] Furthermore, because the silicon component in the organosilicon-modified diol oligomer can contact the boron-containing flame-retardant filler and ceramic filler with a more uniform and larger contact area, the ceramic reaction can occur more quickly during the heating and ablation process, promoting the rapid formation of the borosilicate glass phase (borosilicate solid solution: SiB2O, Si2B2O5) in a short time; and the generated ceramic products can form a two-way mutual transmission network with the carbon skeleton of the ablated carbon layer, which strengthens the ablated carbon layer through a strong bond, making the ablated carbon layer more dense and solid, that is, the mechanical properties of the final coating ablation product are stronger.
[0051] Through the above technical solutions, the present invention has at least the following beneficial effects:
[0052] The flexible ablation-type thermal protective coating prepared by the two-component coating described in this application combines the normal flexibility and toughness of the coating with the strong mechanical properties of the coating ablation products. Under high-temperature ablation, this thermal protective coating can quickly form a robust carbon layer structure containing a borosilicate glass phase. Such ablation products exhibit high mechanical strength and will not break or peel under low-frequency vibration and flame jet erosion. Furthermore, it has low thermal conductivity, providing excellent heat insulation and superior thermal protection performance. It can be applied as thermal protection for equipment and cables near rocket and missile ignition sources, resisting engine vibration breakage and aerodynamic peeling, and will have broad application potential in the field of missile and rocket thermal protection. Attached Figure Description
[0053] Figure 1 The coating samples of Example 1 and Comparative Example 1 were tested at 500 kW / m 2 Comparison of the appearance and microstructure of the coating ablation products after 2 minutes of heat flow radiation;
[0054] Figure 2 The images show the XRD energy distributions of the ablation products of the coatings in Example 1 and Comparative Example 1. Detailed Implementation
[0055] The present invention will be further illustrated by the following embodiments, but the application of the present invention is not limited to the embodiments described.
[0056] Example 1
[0057] This example is a two-component coating, which consists of component A and component B:
[0058] Component A, by weight, comprises 8 parts of organosilicon-modified diol oligomer, 25 parts of polyester diol, 0.2 parts of catalyst, 10 parts of boron-containing flame-retardant filler, 6 parts of ceramic filler, and 40 parts of solvent.
[0059] Component B contains 60 parts by weight of diisocyanate and 30 parts by weight of polyisocyanate.
[0060] In component A of this example:
[0061] The organosilicon-modified diol oligomer is prepared by the following two-step method: In the first step, a cyclic siloxane and bis(3-aminopropyl)tetramethyldisiloxane are reacted at a molar ratio of 1:1.5, with a quaternary ammonium salt as a catalyst (added at 0.13% of the reactant mass) and tetrahydrofuran as a solvent, at 80°C for 10 hours to prepare an amino-terminated siloxane oligomer. The reaction product is washed with deionized water, and the organic phase is distilled under reduced pressure at 80°C. In the second step, the reaction product from the first step is reacted with a cyclic carbonate at a molar ratio of 1:1.2 at 80°C for 6 hours to obtain the organosilicon-modified diol oligomer with a molecular weight Mw=840. In the above preparation steps, the cyclic siloxane is octamethylcyclotetrasiloxane D4, the quaternary ammonium salt is tetrabutylammonium fluoride, and the cyclic carbonate is ethylene carbonate.
[0062] The polyester glycol is poly(1,4-butanediol adipate) diol with a molecular weight (Mw) of approximately 1000. The boron-containing flame-retardant filler contains zinc borate as the boron flame retardant. This filler also includes an organophosphorus flame retardant and melamine pyrophosphate, where the organophosphorus flame retardant is ammonium polyphosphate; the mass ratio of ammonium polyphosphate, melamine pyrophosphate, and zinc borate is 3:1:1. The ceramic filler is a mixture of aluminum dihydrogen phosphate and silica powder in a 2:1 mass ratio, where the silica powder is low-melting-point glass powder (melting point 400-600℃). The catalyst in component A is a bismuth catalyst (bismuth neodecanoate); the solvent for component A is ethyl acetate.
[0063] In component B of this example:
[0064] The diisocyanate is liquefied MDI, specifically Wanhua CDMDI-100L, with an isocyanate mass fraction of 30%. The polyisocyanate is polymeric MDI, specifically Wanhua PM-200, with an isocyanate mass fraction of 32%.
[0065] The above-mentioned two-component coating is used as follows: Mix component A and component B at a weight ratio of 100:11.1, stir evenly, and then spray it onto the surface of the fiberglass fabric substrate in multiple times according to the spraying-drying process. Each spraying is dried at a temperature of 80°C for 15 minutes. Repeat this spraying and drying process until a flexible ablation-type thermal protective coating with a thickness of 3 mm is obtained.
[0066] Example 2
[0067] This example is a two-component coating, which consists of component A and component B:
[0068] Component A, by weight, comprises 12 parts of organosilicon-modified diol oligomer, 18 parts of polyester diol, 0.5 parts of catalyst, 8 parts of boron-containing flame-retardant filler, 7 parts of ceramic filler, and 33 parts of solvent.
[0069] Component B contains 72 parts by weight of diisocyanate and 18 parts by weight of polyisocyanate.
[0070] In component A of this example:
[0071] The organosilicon-modified diol oligomer is prepared by the following two-step method: In the first step, a cyclic siloxane and bis(3-aminopropyl)tetramethyldisiloxane are reacted at a molar ratio of 1:1.7 with a quaternary ammonium salt as a catalyst (added at 0.1% of the reactant mass) and tetrahydrofuran as a solvent at 90°C for 9 hours to prepare an amino-terminated siloxane oligomer. The reaction product is washed with deionized water, and the organic phase is distilled under reduced pressure at 80°C. In the second step, the reaction product from the first step is reacted with a cyclic carbonate at a molar ratio of 1:1 at 70°C for 10 hours to obtain the organosilicon-modified diol oligomer with a molecular weight Mw=943. In the above preparation steps, the cyclic siloxane is one of hexamethylcyclotrisiloxane D3, the quaternary ammonium salt is tetrabutylammonium chloride, and the cyclic carbonate is methyl vinylene carbonate.
[0072] The polyester glycol is polyethylene adipate glycol, with a molecular weight (Mw) of approximately 2015. The boron-containing flame-retardant filler contains borax and sodium borate as the boron flame retardant, and also includes an organophosphorus flame retardant, specifically triphenylphosphonate; the mass ratio of borax, sodium borate, and triphenylphosphonate is 1:2:1. The ceramic filler is a mixture of aluminum dihydrogen phosphate and silica powder in a 2:1 mass ratio; the silica powder is silica micropowder. The catalyst in component A is an organotin catalyst (stannous octoate); the solvent in component A is butyl acetate.
[0073] In component B of this example:
[0074] The diisocyanate is toluene diisocyanate, and the polyisocyanate is HDI trimer, specifically Wanhua HDT-90.
[0075] The above-mentioned two-component coating is used as follows: Mix component A and component B at a weight ratio of 100:12.6, stir evenly, and then spray it onto the surface of the aramid fabric substrate in multiple times according to the spraying-drying process. Each spraying is dried at a temperature of 90°C for 10 minutes. Repeat this spraying and drying process until a flexible ablation-type heat protection coating with a thickness of 3 mm is obtained.
[0076] Example 3
[0077] This example is a two-component coating, which consists of component A and component B:
[0078] Component A, by weight, comprises 5 parts of organosilicon-modified diol oligomer, 20 parts of polyester diol, 0.1 parts of catalyst, 10 parts of boron-containing flame-retardant filler, 8 parts of ceramic filler, and 35 parts of solvent.
[0079] Component B contains 65 parts by weight of diisocyanate and 25 parts by weight of polyisocyanate.
[0080] In component A of this example:
[0081] The organosilicon-modified diol oligomer is prepared by the following two-step method: In the first step, a cyclic siloxane and bis(3-aminopropyl)tetramethyldisiloxane are reacted at a molar ratio of 1:1.8, with a quaternary ammonium salt as a catalyst (added at 0.3% of the reactant mass), and tetrahydrofuran as a solvent, at 60°C for 15 hours to prepare an amino-terminated siloxane oligomer. The reaction product is washed with deionized water, and the organic phase is distilled under reduced pressure at 80°C. In the second step, the reaction product from the first step is reacted with a cyclic carbonate at a molar ratio of 1:1.35 at 100°C for 5 hours to obtain the organosilicon-modified diol oligomer with a molecular weight Mw=862. In the above preparation steps, the cyclic siloxane is octamethylcyclotetrasiloxane D4, the quaternary ammonium salt is tetrabutylammonium fluoride, and the cyclic carbonate is ethylene carbonate.
[0082] The polyester diol is poly(1,4-butanediol adipate) diol with a molecular weight (Mw) of approximately 1000. The boron flame retardant in the boron-containing flame retardant filler is... Triphenyl borateThe boron-containing flame-retardant filler also contains an organophosphorus flame retardant and melamine, wherein the organophosphorus flame retardant is pentaerythritol phosphate; the mass ratio of pentaerythritol phosphate, melamine, and triphenyl borate is 3:1:1. The ceramic filler is a 1:1 (mass ratio) mixture of aluminum dihydrogen phosphate and silica powder; the silica powder is a 2:1 (mass ratio) compound of low-melting-point glass powder (melting point 400-600℃) and mica powder. The catalyst in component A is a bismuth catalyst (bismuth neodecanoate); the solvent in component A is diethyl carbonate.
[0083] In component B of this example:
[0084] The diisocyanate is diphenylmethane diisocyanate (MDI), and the polyisocyanate is a TDI trimer, specifically TT-150B.
[0085] The above-mentioned two-component coating is used as follows: Mix component A and component B at a weight ratio of 100:15, stir evenly, and then spray it onto the surface of the basalt fiber fabric substrate in multiple times according to the spraying-drying process. Each spraying is dried at a temperature of 60°C for 20 minutes. Repeat this spraying and drying process until a flexible ablation-type thermal protective coating with a thickness of 3 mm is obtained.
[0086] Example 4
[0087] This example is a two-component coating, which consists of component A and component B:
[0088] Component A, by weight, comprises 9.8 parts of organosilicon-modified diol oligomer, 25 parts of polyester diol, 0.2 parts of catalyst, 7 parts of boron-containing flame-retardant filler, 6 parts of ceramic filler, and 40 parts of solvent.
[0089] Component B contains 75 parts by weight of diisocyanate and 15 parts by weight of polyisocyanate.
[0090] In component A of this example:
[0091] The organosilicon-modified diol oligomer is prepared by the following two-step method: In the first step, a cyclic siloxane and bis(3-aminopropyl)tetramethyldisiloxane are reacted at a molar ratio of 1:1.6 with a quaternary ammonium salt as a catalyst (added at 0.15% of the reactant mass) and tetrahydrofuran as a solvent at 100°C for 12 hours to prepare an amino-terminated siloxane oligomer. The reaction product is washed with deionized water, and the organic phase is distilled under reduced pressure at 80°C. In the second step, the reaction product from the first step is reacted with a cyclic carbonate at a molar ratio of 1:1.4 at 80°C for 6 hours to obtain the organosilicon-modified diol oligomer with a molecular weight Mw=1032. In the above preparation steps, the cyclic siloxane is decamethylcyclopentasiloxane D5, the quaternary ammonium salt is hexadecyltrimethylammonium chloride, and the cyclic carbonate is propylene carbonate.
[0092] The polyester diol is polycarbonate diol with a molecular weight (Mw) of approximately 1000. The boron flame retardant in the boron-containing flame retardant filler is calcium borate and... Tributyl borate The boron-containing flame-retardant filler also contains an organophosphorus flame retardant, namely 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO); calcium borate, Tributyl borate The mass ratio of DOPO is 2:1:1. The ceramic filler is a 1:1 mass mixture of aluminum dihydrogen phosphate and silica powder; the silica powder is a 2:1 mass mixture of silica micropowder and mica powder. The catalyst in component A is a bismuth catalyst (bismuth neodecanoate); the solvent for component A is ethyl acetate.
[0093] In component B of this example:
[0094] The diisocyanate is a 1:1 (volume ratio) blend of hexamethylene diisocyanate and isophorone diisocyanate, and the polyisocyanate is a 1:1 (volume ratio) blend of TDI trimer (TT-350B) and polymeric MDI (PM-400).
[0095] The above-mentioned two-component coating is used as follows: Mix component A and component B at a weight ratio of 100:5, stir evenly, and then spray it onto the surface of the polyimide fiber fabric substrate in multiple times according to the spraying-drying process. Each spraying is dried at a temperature of 100°C for 15 minutes. Repeat this spraying and drying process until a flexible ablation-type heat protection coating with a thickness of 3 mm is obtained.
[0096] Example 5
[0097] This example is a two-component coating, which consists of component A and component B:
[0098] Component A, by weight, comprises 15 parts of organosilicon-modified diol oligomer, 15 parts of polyester diol, 0.4 parts of catalyst, 5 parts of boron-containing flame-retardant filler, 7 parts of ceramic filler, and 30 parts of solvent.
[0099] Component B contains 68 parts by weight of diisocyanate and 20 parts by weight of polyisocyanate.
[0100] In component A of this example:
[0101] The organosilicon-modified diol oligomer is prepared by the following two-step method: In the first step, a cyclic siloxane and bis(3-aminopropyl)tetramethyldisiloxane are reacted at a molar ratio of 1:2, with a quaternary ammonium salt as a catalyst (added at 0.5% of the reactant mass), and tetrahydrofuran as a solvent, at 120°C for 8 hours to prepare an amino-terminated siloxane oligomer. The reaction product is washed with deionized water, and the organic phase is distilled under reduced pressure at 80°C. In the second step, the reaction product from the first step is reacted with a cyclic carbonate at a molar ratio of 1:1.5 at 90°C for 7 hours to obtain the organosilicon-modified diol oligomer with a molecular weight Mw = 1011. In the above preparation steps, the cyclic siloxane is decamethylcyclopentasiloxane D5, the quaternary ammonium salt is hexadecyltrimethylammonium chloride, and the cyclic carbonate is propylene carbonate.
[0102] The polyester diol is polybutylene sebacic acid diol, with a molecular weight (Mw) of approximately 3000. The boron flame retardant in the boron-containing flame retardant filler is... Tributyl borate The boron-containing flame-retardant filler also contains an organophosphorus flame retardant, wherein the organophosphorus flame retardant is ammonium polyphosphate and triphenylphosphonate. Tributyl borate The mass ratio of ammonium polyphosphate and triphenylphosphonate is 2:1:1. The ceramic filler is a mixture of aluminum dihydrogen phosphate and silica powder in a mass ratio of 1:1.5; the silica powder is a 1:1 mass ratio compound of low-melting-point glass powder (melting point 400-600℃) and silica micropowder. The catalyst in component A is a tertiary amine catalyst (N,N-dicyclohexylmethylamine); the solvent in component A is dimethyl carbonate.
[0103] In component B of this example:
[0104] The diisocyanate is a 1:1 (volume ratio) blend of toluene diisocyanate and isophorone diisocyanate, and the polyisocyanate is a 1:1 (volume ratio) blend of HDI trimer (Wanhua HDT-LV) and polymeric MDI (Wanhua PM-200).
[0105] The above-mentioned two-component coating is used as follows: Mix component A and component B at a weight ratio of 100:12.4, stir evenly, and then spray it onto the surface of the fiberglass fabric substrate in multiple times according to the spraying-drying process. Each spraying is dried at a temperature of 70°C for 20 minutes. Repeat this spraying and drying process until a flexible ablation-type thermal protective coating with a thickness of 3 mm is obtained.
[0106] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Based on the present invention, and through the above description, those skilled in the art can make various changes and modifications without departing from the technical concept of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
[0107] The principles of the above embodiments are as follows:
[0108] The organosilicon-modified diol oligomer in component A is an oligomer with Si-O-Si segments in its molecular chain and C-OH-terminated ends. It has good compatibility with polyester diol and can be uniformly dispersed in the coating as a film-forming substance, and can uniformly coat each solid filler component.
[0109] In the heat-protective coating prepared by cross-linking and curing components A and B, the organosilicon-modified diol oligomer uniformly coated with solid filler has siloxane segments that can increase the flexibility of the coating matrix, making the heat-protective coating flexible, foldable and bendable under normal conditions.
[0110] Furthermore, because the silicon component in the organosilicon-modified diol oligomer can contact the boron-containing flame-retardant filler and ceramic filler with a more uniform and larger contact area, the ceramic reaction can occur more quickly during the heating and ablation process, promoting the rapid formation of the borosilicate glass phase (borosilicate solid solution: SiB2O, Si2B2O5) in a short time; and the generated ceramic products can form a two-way mutual transmission network with the carbon skeleton of the ablated carbon layer, which strengthens the ablated carbon layer through a strong bond, making the ablated carbon layer more dense and solid, that is, the mechanical properties of the final coating ablation product are stronger.
[0111] Comparative Example 1
[0112] This example, based on Example 1, removes the organosilicon-modified diol oligomer from component A of Example 1 to demonstrate the effects of adding the organosilicon-modified diol oligomer. Furthermore, to ensure the smooth fabrication of coatings and paints, the following adjustments are made:
[0113] The 8 parts of organosilicon-modified diol oligomer in component A of Example 1 were removed; the 1,4-butanediol adipate (Mw=1000) in component A was adjusted to 33 parts; and the ceramic filler was adjusted to 7 parts.
[0114] The ceramic filler includes: 4 parts aluminum dihydrogen phosphate, 2 parts low melting point glass powder, and 1 part silica micro powder (2000 mesh).
[0115] The weight ratio of component A to component B during application is 100:10.3;
[0116] The rest is the same as in Example 1.
[0117] Mechanical properties were tested on the coating samples of the above embodiments and comparative examples. The Shore hardness of the coating was measured according to GB / T 531.1-2008 standard, and the tensile elongation and tensile strength of the coating were measured according to GB / T 531.1-2008 standard.
[0118] The flame retardancy ratings of the coatings in each embodiment and comparative example were measured according to the UL-94 flammability test standard.
[0119] Coating samples from each embodiment and comparative example were taken and subjected to a 500 kW / m 2 After thermal ablation (over 1000℃) for 2 minutes, the collapse phenomenon of the coating ablation product was observed on a vibration table (20Hz, 2mm, 5min); the compressive strength of the coating ablation product was tested according to GB / T 1041-2008 standard; and the thermal conductivity of the coating ablation product was measured according to GB / T 8722-2019 (flash method) standard.
[0120] All embodiments and comparative examples were uniformly sprayed to prepare 3mm thick coating samples. The samples were then burned with an oxyacetylene flame for 20s. The temperature rise on the back side of the coating sample was measured. The average value of three parallel tests was taken to obtain the thermal protection performance of the coating.
[0121] The test results for the above tests are shown in Table 1 below; the coating samples of Example 1 and Comparative Example 1 were tested at 500 kW / m 2 A comparison of the appearance and SEM (scanning electron microscope) morphology of the coating ablation products after 2 minutes of heat flow (over 1000℃) radiation is shown in the appendix. Figure 1 The coating ablation products of Example 1 and Comparative Example 1 were analyzed by XRD energy dispersive spectroscopy (EDS), see attached figure. Figure 2 .
[0122] Table 1:
[0123]
[0124] As shown in Table 1, the most significant advantage of the flexible ablation-type thermal protective coatings provided in the embodiments of the present invention is that the ablation products of the coating have excellent mechanical properties, and the coating can also ensure that it has normal room temperature flexibility before ablation. In contrast, the sample of Comparative Example 1 did not contain organosilicon-modified diol oligomers. Although its coating also has a certain degree of flexibility at room temperature (inferior to the embodiments), the mechanical properties of its ablation products are very poor; it breaks easily upon contact, making it impossible to measure the compressive strength value using a mechanical testing machine, and it also fails the vibration table test. In the thermal protection performance test of oxyacetylene flame burning, the ablation products of this coating gradually detach due to the scouring effect of the flame airflow, resulting in poor performance. Therefore, in actual engine vibration and pneumatic stripping application environments, it cannot provide effective thermal protection.
[0125] The coatings provided in each embodiment can generate a borosilicate glass phase through a vitrification reaction during the heating and ablation process by combining organosilicon-modified diol oligomers with boron-containing flame-retardant fillers and ceramic fillers. This vitrified product forms a two-way interconversion network with the carbon skeleton of the ablated carbon layer, strengthening the ablated carbon layer through a strong bond, making the ablated carbon layer denser and more robust. Figure 1Both the macroscopic photographs and SEM microscopic images show that the ablation layer obtained in Example 1 is dense and has a "glossy" texture, giving it good ablation carbon layer strength. It can pass the vibration test on the vibration table, with a compressive strength of over 1.1 MPa. In the oxyacetylene flame test, such a coating ablation product can also easily resist the erosion of the flame gas flow, thus providing good thermal protection, with the temperature rise on the back side all within 30°C.
[0126] Depend on Figure 2 It can be seen that the ablation product of the coating in Comparative Example 1 only has a broad, blunt peak belonging to the amorphous carbon structure, while in the ablation product of the coating in Example 1, obvious peaks of a low-crystallinity borosilicate phase appear at 20.8°, 26.6°, and 29.6°. In addition, some weak, sharp peaks can also be observed, indicating the formation of a low-crystallinity ceramic phase structure. This further confirms that the thermal protective coating proposed in this invention can form a robust carbon layer structure containing a borosilicate glass phase during a short ablation process.
Claims
1. A two-component coating, characterized in that: It consists of component A and component B; Component A comprises, by weight, the following: 5-20 parts of organosilicon-modified diol oligomers; 10-30 parts of polyester glycol; 0.1-1 part of catalyst; 5-15 parts of boron-containing flame-retardant filler; 5-10 parts of ceramic filler; 20-60 parts solvent; The boron flame retardant in the boron-containing flame retardant filler is one or more of zinc borate, borax, sodium borate, calcium borate, triphenyl borate, and tributyl borate; the ceramic filler is aluminum dihydrogen phosphate and silica powder. Component B comprises, by weight, the following: 50-90 parts of diisocyanate; 10-40 parts of polyisocyanate.
2. The two-component coating according to claim 1, characterized in that: Component A comprises, by weight, the following: 5-15 parts of organosilicon-modified diol oligomer; 15-25 parts of polyester glycol; 0.1-0.5 parts of catalyst; 5-10 parts of boron-containing flame-retardant filler; 6-8 parts of ceramic filler; 30-40 parts solvent; Component B comprises, by weight, the following: 60-75 parts of diisocyanate; 15-30 parts of polyisocyanate.
3. The two-component coating according to claim 1, characterized in that, The organosilicon-modified diol oligomer is prepared by a two-step method: the first step involves reacting a cyclic siloxane with bis(3-aminopropyl)tetramethyldisiloxane at a molar ratio of 1:1.5-2, using a quaternary ammonium salt as a catalyst, at 60-120°C for 8-15 hours; the second step involves reacting the reaction product from the first step with a cyclic carbonate at a molar ratio of 1:1-1.5, at 70-100°C for 5-10 hours to obtain the organosilicon-modified diol oligomer.
4. A two-component coating according to claim 3, characterized in that: The cyclic siloxane is one of hexamethylcyclotrisiloxane D3, octamethylcyclotetrasiloxane D4, and decamethylcyclopentasiloxane D5; The quaternary ammonium salt is one of tetrabutylammonium chloride, tetrabutylammonium fluoride, and hexadecyltrimethylammonium chloride; The cyclic carbonate is one of methyl vinylene carbonate, ethylene carbonate, and propylene carbonate.
5. A two-component coating according to claim 1, characterized in that: The polyester diol is one of polyethylene adipate diol, 1,4-butanediol adipate diol, polycarbonate diol, and polybutylene sebacate diol, with a molecular weight Mw of 1000-3000.
6. A two-component coating according to claim 1, characterized in that: The boron-containing flame-retardant filler also contains an organophosphorus flame retardant, which is one or more of ammonium polyphosphate, pentaerythritol phosphate, triphenylphosphonate, and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO).
7. A two-component coating according to claim 1, characterized in that: The silica powder is one or more of low-melting-point glass powder, mica powder, and silica micro powder.
8. A two-component coating according to claim 1, characterized in that: The diisocyanate is one or more of toluene diisocyanate, diphenylmethane diisocyanate, liquefied MDI, hexamethylene diisocyanate, and isophorone diisocyanate; The polyisocyanate is one or more of TDI trimer, HDI trimer, and polymeric MDI.
9. A method of using a two-component coating as described in any one of claims 1-8, characterized in that: The process involves mixing component A and component B at a weight ratio of 100:5-15, spraying the mixture onto the substrate surface multiple times using a spraying-drying process, and drying each coat at a temperature of 60-100℃ for at least 10 minutes to obtain a flexible ablation-type thermal protective coating.
10. A flexible ablation-type thermal protective coating prepared by the method described in claim 8, characterized in that: The thermal protective coating has a Shore A hardness of less than 50, an elongation at break of more than 100%, a tensile strength of more than 4 MPa, and a UL-94 flame retardancy rating of V-0. The thermal protective coating can form a coating ablation product containing a borosilicate glass phase within 2 minutes under high temperature ablation above 1000℃. The thermal conductivity of the coating ablation product is 0.5-1.2 W / m·K, and the compressive strength of the coating ablation product is above 1.1 MPa.